Nutritional Status and Non-Diet Associated Factors of Hospitalized Heart-Failure Elderly Patients - Shirin Hosseini; Ali Keshavarz; Ahmad Amin; Majid Maleki; Homan Bakhshandeh Abkenar (University of Social Welfare & Rehabilitation Sciences, 2010)
Objectives: The aim of this study was to assess nutritional status and identify the most significant MNA-items (Mini Nutritional assessment) to accelerate the determination of nutritional risk of heart-failure in elderly patients. Methods and Materials: The present research was a cross-sectional descriptive analytical survey on hospitalized heart- failure elderly patients (n=225). The sampling method was enrolled nonrandomly. The MNA questionnaires (18 items) were used for nutritional assessment. Results: Based on the MNA questionnaire, 9.8% of the elderly were malnourished, 80.9% were at risk of malnutrition and 9.3% were well-nourished. Conclusion: Regarding the factors related to nutritional status of heart failure elderly patient, it is indicated that bed sore, the ability of eating, self-view of nutritional status and self-rated health status relative to peers had significant relationship with the nutritional status according to MNA (P<0.005). Regarding high prevalence of vulnerable or malnourished hospitalized elderly, nutritional intervention is necessary.